Effect of doping with In2O3 on some properties of ZnO: SnO2 thin film prepared by thermochemical hydrolysis method and its use in gas sensing applications - et. al., Ali H . Abdulzahra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aims to prepare thin films from (ZnO: SnO2) mixture. Undoped membranes (ZnO: SnO2) dotted with (In2O3) and with a percentage of doping (3.5, 7%) based on chemical thermal dissolution (CSP) technology, by depositing them on glass floors at a temperature of 400 degrees Celsius and at a rate of one spray for four seconds in every one minute. To obtain thin films with high homogeneity and transparency, in order to impose a study of the structural properties of the prepared films and the possibility of these films responding as a gas sensor.